Deaths in children during an outbreak of hand, foot and mouth disease in Peninsular Malaysia--clinical and pathological characteristics - Shekhar, K.; Lye, M.S.; Norlijah, O.; Looi, L.M.; Khuzaiah, R.; Marzuki, I. (Malaysian Medical Association, 2005)
From July through December 1997, 11 previously healthy children in Peninsular Malaysia succumbed to an illness clinically characterised by an acute severe refractory left-ventricular failure, following a brief prodromal illness, in the midst of an outbreak of hand, foot and mouth disease (HFMD), similar to the reported experience in Sarawak and Taiwan. Retrospective reviews of the clinical features and results of laboratory, pathological and virological investigations of cases were conducted. The median age of the 11 case-patients was 31 months (range, 13 to 49 months); 6 were males. A brief prodromal illness of 3 days (range, 2 to 5 days) was characterised by fever (axillary temperature > 38 degrees C) (100%), oral ulcers (72%), extremity rashes (45%) and significant vomiting (55%). Upon hospitalisation, 7 of 11 case-patients had features suggestive of cardiogenic shock, while 4 of 11 case-patients developed shock during hospitalisation as evidenced by marked sustained tachycardia (heart rate > or = 180 beats per minute), poor peripheral pulses and peripheral perfusion, mottled extremities, pulmonary oedema (haemorrhagic pulmonary secretions in 8 of 11 cases during tracheal intubation, often precipitated by conservative crystalloid boluses, and radiographic evidence of acute pulmonary oedema in 5 of 7 cases) and markedly impaired left ventricular function on echocardiographic examination (7 of 7 cases). Three of 4 case-patients had aseptic meningitis while one case-patient also had an acute flaccid paraparesis. Despite supportive therapy, death occurred within a median of 13.4 hours following hospitalization. Post-mortem findings (all 8 specimens examined) consistently demonstrated brain-stem encephalitis with foci of neuronal necrosis and micro-abscesses. None of the 11 specimens examined revealed histological evidence of myocarditis. Enterovirus 71 (EV71) was detected in 10 of 11 case-patients, many (7) from various sterile tissue sites (5 from central nervous tissues). No other viruses were isolated or identified. Clinical features and pathological studies closely paralleled the reported experience in Sarawak and Taiwan. The uniform necropsy findings of necrotizing brain-stem encephalitis coupled with essentially normal myocardial histology, in concert with the concurrent and consistent detection of EV71 points to a primary EV71 encephalitis; as yet unclear neurogenic mechanisms may account for the cardiovascular manifestations.